2020
DOI: 10.23889/ijpds.v5i1.1150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Study Duration and Outcome Measurement Frequency on Estimates of Change for Longitudinal Cohort Studies in Routinely-Collected Administrative Data

Abstract: Introduction: When designing prospective and retrospective longitudinal cohort studies, investigators must make decisions about study duration (i.e. length of follow-up) and frequency of outcome measurement. The impact of these decisions have been previously investigated in the prospective setting, but have not been described for retrospective cohort studies.   Objectives: To examine the impact and potential challenges of longitudinal design decisions in retrospective cohort studies and illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Our review also showed that studies conducted for more than 6 months reported a higher decrease in HIV testing rate than those performed for less than or equal to 6 months, corroborating the influence of study duration on the research findings [ 79 ]. Studies conducted for more than 6 months likely included many stay-at-home orders, which could have impacted the provision of and access to HIV testing.…”
Section: Discussionsupporting
confidence: 78%
“…Our review also showed that studies conducted for more than 6 months reported a higher decrease in HIV testing rate than those performed for less than or equal to 6 months, corroborating the influence of study duration on the research findings [ 79 ]. Studies conducted for more than 6 months likely included many stay-at-home orders, which could have impacted the provision of and access to HIV testing.…”
Section: Discussionsupporting
confidence: 78%
“…Decreased sample size has negative effects on the accuracy of estimated changes and the statistical power of the study. (Feely et al., 2020) Of the studies with known duration of the study, 4 studies had a duration of ≤ 5 years (Shaw et al., 2017; Briones‐Buixassa et al., 2019; Gunnarsson et al., 2015; Pust et al., 2020) and 3 studies had a duration of ≥ 5 years (Eid et al., 2022; Horton et al., 2022; Nielsen et al., 2014). Small sample size associated with the included studies may limit the generalizability of the study outcomes, and ultimately this systematic review (Jiang et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Even in smaller sample sizes, the precision of study outcomes may improve with longer study durations. Decreased sample size has negative effects on the accuracy of estimated changes and the statistical power of the study (Feely et al, 2020). Of the studies with known duration of the study, 4 studies had a duration of ≤ 5 years(Shaw et al, 2017;Briones-Buixassa et al, 2019;Gunnarsson et al, 2015;Pust et al, 2020) and 3 studies had a duration of ≥ 5 years(Eid et al, 2022;Horton et al, 2022;Nielsen et al, 2014).…”
mentioning
confidence: 99%
“…(10) Longer duration of intervention can yield, an increased number of precise outcomes. (83) It is also suggested to conduct the research with a larger number of study group diagnosed with PCOS, as larger sample size can prevent false positive results and prevent misinterpretation of the result obtained. (80,81) Also, it is best if the research could focus into multi-ethnic or multi-centered groups in order to confirm the findings of the research as it can help to prove to be effective to all PCOS women populations.…”
Section: Conclusion and Future Recommendationmentioning
confidence: 99%